Pengembangan lembar kerja berbasis pendekatan scientific kelas IV sekolah dasar - Diana Endah Handayani; Amalia Aljani (Universitas Sarjanawiyata Tamansiswa, 2018)
This research has succeeded in developing student worksheet based on scientific approach to fourth grade students of Elementary School. This research is based on the implementation of the 2013 curriculum emphasizes the theme as a unifying of various subjects and prioritizes learning that aims to activate students. But all this time the teacher only rely on teacher books and student books and supporting use of student worksheets from publishers. The student worksheet has not been able to balance the content of the expected curriculum. The student worksheet contains a brief summary of the subject and practice questions. Thus, the problem in this research is how the feasibility of development of student worksheet based on scientific approach of sub theme of Energy Source? The type of research undertaken is research development (Research and Development) with Borg & Gall learning system design model. This study was piloted in class IV SD Negeri 01 Podosugih as many as 10 students. From this research result of product of Student Worksheet based on scientific approach to support implementation of curriculum 2013 in sub theme sub theme 2 theme of Energy Source in fourth grade of elementary school. based on the validation result through 2 stages: a) the result of validation of the material of learning material of phase I obtained the average of 53.12 criteria less feasible and stage II 77,08 criterion is feasible. b) the result of validation of expert evaluation of learning media of phase I get the average, 78,33 eligible criterion and stage II 91,67 criterion very feasible. c) teacher response earned an average of 91.00 very positive criteria. d) result of questionnaire student response get average 88,10 with criterion very positive. The researcher's suggestion is that students are accustomed in scientific-based learning, in order to stimulate students' activeness and critical thinking, so that time allocation can be done well, and student worksheet based on scientific approach can be used for further research.